Hubungan Pendampingan Persalinan Dengan Lama Persalinan Kala II Di BPS Enok Desa Jarangan Kecamatan Rejoso Kabupaten Pasuruan - Aprilian Maya Rulita (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2009)
the purpose of the study is knowing the relation between labor accompanion and the labour duration of the second duration in BPS Enak Rejoso in Grati District and Pasuruan Regency. the result of the study showed that the result of exact fisher test was p = 0,016 which meant that p was bigger than 0,01 and less than 0,05 so that How was rejectted and H1 was received. it meant that there was a relation between labour accompanion and labour duration of the second period